A Comparison of Attitudes About Paternal Child Support Payments in the United States and South Korea. Issue 1 (2nd January 2023) - Ko, Kwangman; Ganong, Lawrence; Kang, Youngjin; Chapman, Ashton
ABSTRACT: We compared attitudes about child support between the United States and South Korean respondents, using a multiple segment factorial vignette to gather quantitative and qualitative data from 132 Americans and 132 South Koreans. South Koreans were more likely than U.S. respondents to think child support should be paid. Respondents in both countries thought fathers should pay more child support when mothers had sole custody than when both parents shared custody. Remarriage, combined with custody, affected respondents' attitudes. The primary rationale of U.S. respondents focused on issues of fairness, while Koreans highlighted fathers' responsibility and obligation. Cross-cultural differences in attitudes regarding child support payments, and their implications for support compliance rates in the United States and South Korea, are discussed.